The Effectiveness Test of Bangun-Bangun Leaves Extract (Plecthranthus Ambonicus) Against Streptococcus Pyogenes and Salmonella Typhi Bacteria - Yulizal, Ok; Windi Anggriani; Stella Retta Marina; Ayu hasanah (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2020)
Background Bangun-bangun leaves (Plectranthus amboinicus) are part of theLamiaceae family. (1) (1) Bangun-bangun leaves have a characteristic aromatic leavesaroma used as a medicinal plant (2). According to research conducted by (Dalimuntheet al., 2016) to find the use of this plant as an antibacterial because it containscompounds such as flavonoids, tannins, tripenoids, saponins, and essential oils. Onthe bangun-bangun leaves there is carvacrol, which is an essential component that hasantibacterial activity in positive or negative gram bacteria. streptococcus pyogenesbacteria are vectors of suppurative infectious diseases and other diseases such aspharyngitis. While salmonella typhi bacteria is a vector of the disease which is usuallycalled typhus and the medical language is typhoid fever. The purpose of this study wasto determine that the bacteria salmonella typhi and streptococcus pyogenens can beinhibited by the leaves extract. The benefit of this research is to increase publicunderstanding and knowledge in the use of bangun-bangun leaves. The method usedin this study is an experimental method and post test only controlled group design. Forthe concentration used, namely 5%, 10%, 15%, 20%, 25% and this strength test is doneby inserting the extract into a petri dish that has a bacterial culture. Data processinguses one-way ANOVA with the aim of comparing each variable. To see the extractagainst bacteria. The results showed that there were variations in the diameter of theinhibition zone formed by the concentration of the extract. And the most effectiveconcentration to inhibit streptococcus pyogenes bacteria was a concentration of 25%,the inhibition zone diameter was 19.5mm, while salmonella typhi bacteria had aconcentration of 25% and the inhibition zone diameter was 37.7m